Styl jako kategoria lingwistyki międzykulturowej - Kiklewicz, Aleksandek (Stylistyka, 2020)
The aim of the paper is to discuss the perspectives of the functional stylistics. Functional-stylistic approach is based on the idea of the socio-cultural determinants of the functional styles. Each functional style represents a distinct fragment of social reality (social context, by P. Sztompka, or functional system, by M. Fleischer) and stylistic studies are connected with intercultural linguistics. The natural consequence of this theoretical assumption is a need for two-level social stratification of language varieties: category of the functional style and the culturally marked substyles. Linguistic study of substyles (as well as study of the culturally marked varieties and discourses) should be an essential part of the functional stylistics. The intercultural linguistics contributes to the development of the knowledge about the mutual conditioning of language and culture.